The Impact of Early Marriage Traditions - Ahmadi Ahmadi; Nur Asliah; Erwin Pane (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This study aims to analyze the forms of impact of early marriage and the factors behind its sustainability in society. The method used is qualitative research with a literature study approach, through analysis of books, journal articles, research reports, and relevant policy documents. The results show that early marriage has the potential to hinder access to education, increase reproductive health risks, trigger psychological unpreparedness in marriage, and strengthen the cycle of poverty and gender inequality. In addition, the practice of early marriage also has an impact on the high divorce rate and the weak quality of childcare. This study concludes that the tradition of early marriage requires comprehensive handling through educational, social, and legal policy approaches oriented to the protection of children's rights and the improvement of family welfare.